PENGEMBANGAN MEDIA TEKNOLOGI ASISTIF DALAM MENINGKATKAN KEMANDIRIAN BANGUN TIDUR MAHASISWA TUNARUNGU DI UNIVERSITAS NEGERI MALANG - Wijayanti, Ajeng Putri Kusbinang; Ediyanto, Ediyanto; Kustiawan, Usep; Adi, Eka Pramono; Irvan, Muchamad (Universitas Muria Kudus, 2023)
This study aims to produce assistive technology products in the form of vibrating pillows with performance components designed according to the needs of deaf college students in increasing independence when they wake up. The research method used is research and development or Research and Development (RD) with the Sustainable Development Model in Educational Research. Data collection techniques in the form of observation, questionnaires, trials and documentation. The research subjects were deaf college students at State University of Malang. The research design was carried out twice with 3 media experts and 7 respondents. Data analysis by media experts using the percentage formula produces a value of 95% which means the product is valid. After the product was declared valid, data analysis was carried out on 7 respondents in the form of a product performance effectiveness test and a different test with the initial/before survey and the final/after product use survey. Analysis of product performance effectiveness test data in two days of trial results increased from 95% to 97.8%. Non-Parametric Willcoxon Signed Ranks Test data analysis using SPSS, showed that there was no decrease in value from the initial survey to the end because Negative Ranks showed a value of 0. There was an increase in self-reliance marked by Positive Ranks indicating a value of 7. The results showed that the hypothesis was accepted by showing the data different test Wilcoxon signed ranks test obtained Z count = -2.375 and α = 0.05, then sig = 0.018. This shows that Sig 0.018 is smaller than 0.05 (0.018 0.05). These results explain that the product has a good effect on changes in the independence ability in wakening for deaf college students.